First record of the mating behaviour of the spotted surubim Pseudoplatystoma corruscans in the Uruguay River. Issue 4 (23rd August 2020) - Pachla, Lucas A.; Hartmann, Paula B.; Massaro, Marthoni V.; Bastian, Rodrigo; Pelicice, Fernando M.; Reynalte‐Tataje, David A.
Abstract: The spotted surubim Pseudoplatystoma corruscans is a large migratory catfish native to the La Plata and San Francisco basins. Nonetheless, its reproductive dynamics and behaviour remain poorly understood. This brief note provides the first record of the mating behaviour of P. corruscans in natural conditions. This behaviour was observed in the main channel of the Middle Uruguay River (Brazil). A school of approximately 25 fish, 5 females (with protruding abdomen and larger body size) and 20 males, were followed and videotaped. The largest female led the school, followed by other fish. Some males disputed repeatedly the posterior region of the females, whereas other males continuously repelled them. Eventually, some males, apparently exhausted, floated belly up. During this event, males were in a state of pronounced agitation, and some had abrasions in the head. Polygamy characterized the mating behaviour of P. corruscans .